The Profile of Vocabulary Mastery and Translation Ability of Junior High School Students in Pangkep - Sri Rahayu Marwati; Sahril Nur; A. Muliati (Journal of Excellence in English Language Education, 2022)
The aims of this study are to determine the vocabulary mastery and the ability to translate of junior high school students in Pangkep also whether vocabulary knowledge and translation competence are linked. This study employed a quantitative approach. This article only contains the third research question. The data of this research was collected through a test. Cluster-stratified random sampling was used to obtain the sample. In this study, 108 seventh-grade students in Pangkep were recruited from three accredited schools: SMP 1 Pangkajene, SMP 3 Bungoro, and SMP 5 Bungoro. The Pearson correlation results for vocabulary mastery and translation ability at A-certified schools are 0.653, which is 0.61-0.80, indicating a high correlation. Pearson correlation -0.595 is in the interval 0.41-0.60 for accredited B schools so that the correlation is obtained, and 0.112 is in the interval 0.00-0.20 for accredited schools so that no correlation is found.